Deficiency in WDFY4 reduces the number of CD8+ T cells via reactive oxygen species-induced apoptosis. (November 2021) - Li, Yan; Li, Jiangxia; Yuan, Qianqian; Bian, Xianli; Long, Feng; Duan, Ruonan; Gao, Fei; Gao, Shang; Wei, Shijun; Wang, Anran; Liu, Ai; Li, Xi; et al.
Highlights: WDFY4 modulates T cell fate via reactive oxygen species-induced apoptosis. WDFY4 participates in apoptosis via the p53 and ERK pathways. Wdfy4 influences the proliferation of CD8 + T cells. Abstract: WDFY4 (WD repeat and FYVE domain-containing 4) is a susceptibility gene involved in several autoimmune diseases and plays an important role in the immune system. However, it is not clear how WDFY4 affects T cells. We have generated a Wdfy4 -knockout mouse and found that selective deficiency of Wdfy4 in T cells led to a reduction in the number of CD8 + T cells in the periphery, thus promoting tumor growth when mice were challenged with a transplantable tumor. Moreover, conditional ablation of Wdfy4 in T cells enhanced the apoptosis of CD8 + T cells and increased the intracellular levels of reactive oxygen species accompanied by the upregulation of Nox2 . Mechanistically, the decrease in the CD8 + T-cell numbers in Wdfy4 -knockout mice was associated with activation of the p53 pathway and inhibition of the extracellular signal-regulated kinase pathway. In addition, WDFY4 participated in cell proliferation. In conclusion, our results elucidate the biological role of WDFY4 in apoptosis and establish a link between WDFY4 and T cells.